Analisis Pengelolaan Keuangan Dana Desa (Studi Di Desa Wonorejo Kecamatan Singosari Kabupaten Malang) - Ni Kadek Sekar Ayu Saraswati Yudana; Khojanah Hasan; Endah Puspitosarie (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
Village financial managementis an activity that includes the process of administering a budget originating from the APBN which will be distributed to each village which will then be monitored and held accountable for its use. Managed village financial management must be carried out openly to create transparency. In the Permendagri Number 20 of 2018 concerning the management of village funds with the planning, budgeting and implementation stages of activities as well as budgeting, administration, reports and responsibilities must be carried out in a participatory, transparent, accountable and orderly manner as well as budget discipline. Research using descriptive qualitative analysis. This study intend to find out whether the financial management of village funds in Wonorejo Village is in accordance with the standards in the Permendagri Number 20 of 2018 concerning village financial management or not. The object of this research was conducted in Wonorejo Village, Singosari District, Malang Regency. The results of the study show that the financial management of village funds in Wonorejo Village is in accordance with the Permendagri Number 20 of 2018 concerning village financial management.